Optimal conditions for extracting bioactive compounds from leaves of Cleistocalyx operculatus roxb using an enzyme cocktail - Dinh Giap, Vu; Thi Cam Van, Do; Dinh Duy, Vu; Kim Dung, Vu; Thi Hai Ha, Nguyen (Journal of Forestry Science and Technology, 2023)
In recent years, both scientists and food producers have shown great interest in natural compounds with high biological activity. Leaves of Cleisto (Cleistocalyx operculatus Roxb) contain polyphenolic compounds with high biological activity, including flavonoids such as quercetin, kaempferol, myricetin, tannins, and other phenolic compounds. These compounds are highly beneficial for human health due to their potent antioxidant activity and various other biological activities. These polyphenols play a crucial role in protecting the body against various diseases caused by free radicals. They have the ability to prevent cellular and DNA damage. Polyphenols derived from mulberry leaves have significant potential for the production of high-value functional foods. In this study, the total polyphenol content, and antioxidant activity of leaves of Cleisto were studied. These bioactive compounds were shown to be more abundant in the dried extract of Cleisto than in the control sample (enzymes inactivated) following 21 hour of incubation with laccase and celluclast® 1.5L (each enzyme at least 30 U/gram dry biomass) at 45oC, pH 5.0. The highest total polyphenol content and antioxidant activity achieved was 23.95 mg GAE/gds and 80.32%, respectively. Therefore, enzyme-assisted extraction technique has various benefits and is a potential method to obtain bioactive chemicals from leaves of Cleisto.